Analysis of the citation impact of national journals toward SCIE journals on JCR ranking - Kim, Byungkyu; Kim, Youngseek; Kang, Jihoon (Malaysian Journal of Library and Information Science, 2018)
The prior studies in the citation analyses of Korean natural science and engineering journals found that they have cited SCIE (Science Citation Index Extended) journals significantly. This research investigated the citation impact of the Korean natural science and engineering journals (from 2009 to 2014) toward SCIE journals in terms of JCR (Journal Citation Reports) ranking changes. First, this research analyzed the cited numbers and citation age by subject and journal through the citation analysis of the cited SCIE journals. Second, this research created the co-citation networks of journals and subjects by using co-citation analysis of SCIE journals. Based on the same method, we also assessed the network centrality measures and compared the citation numbers in each journal. Third, this research analyzed the changes in journal ranking in SCIE journal citation index by reflecting the citations of Korean natural science and engineering journals into JCR. Our results indicate that engineering has higher cited numbers, smaller peak-time, and cited half-time values than natural science. These results mean the journal articles in engineering are more quickly consumed and decreased than natural science journals, respectively. Second, this research visualized the co-citation network of SCIE journals and subject areas based on the Korean journals, and it also measured the network centrality in journals and subjects. Third, this research found that the existing journal Impact Factor (IF) (2 years) has been changed significantly if we apply the Korean journal citations into JCR in 2014, and there are significant changes in JCR journal rankings in engineering and natural science. This research shows the impact of Korean journals on SCIE journals, and the results of this study can be used for the future evaluation of journals. The practical implications were presented for Asian countries as well as Korea to develop their own JCR rankings and for their academic libraries to provide better scholarly services.